Parton distribution function for quarks in an s-channel approach - Hautmann, F; Soper, D (2007)
We use an s-channel picture of hard hadronic collisions to investigate the parton distribution function for quarks at small momentum fraction x, which corresponds to very high energy scattering. We study the renormalized quark distribution at one loop in this approach. In the high-energy picture, the quark distribution function is expressed in terms of a Wilson-line correlator that represents the cross section for a color dipole to scatter from the proton. We model this Wilson-line correlator in a saturation model. We relate this representation of the quark distribution function to the corresponding representation of the structure function FT(x,Q2) for deeply inelastic scattering. © 2007 The American Physical Society.